A review on electrical capacitance tomography sensor development - Abd. Rahman, Noor Amizan; Abdul Rahim, Ruzairi; Mohd Nawi, Abdullah; Leow, Pei Ling; Pusppanathan, Jaysuman; Mohamad, Elmy Johana; Chan, Kok Seong; Mohammad Din, Shahrulnizahani; Nor Ayob, Nor Muzakkir; Mohd Yunus, Fazlul Rahman (Penerbit UTM Press, 2015)
Electrical Capacitance Tomography (ECT) detects changes in the distribution of transparency in enclosed areas or pipes. Until now, various methods have been used to determine the optimum ECT sensor for a particular application. Some important parameters that affect the sensitivity of the sensor cannot be ignored. Design factors discussed in this paper study the needs in industry by producing the best image, without affecting the operation of the process. From previous studies many parameters influence the quality and effectiveness of an ECT sensor. The parameters that play important roles in ECT sensor design include the thickness and type of material in the pipe wall between the electrodes and the sensing zone, the thickness and material of the pipe wall separating the electrodes and the screen, the size of the electrodes, the guarding used, example radial guards or plane axial guards, and whether end guards are used. Other matters of concern regarding the dimension and the distance between the electrodes with guardians it is important design factor. Electrodes positioned either inside or outside the vessel will affect the cost factor design to the type of system to be used. This overview of the study is a basic guide for the essential requirements for an ECT sensor system design.